2015
DOI: 10.3892/ijmm.2015.2170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc on high glucose-induced epithelial-to-mesenchymal transition in renal tubular epithelial cells

Abstract: Zinc (Zn) as an essential dietary element has been indicated in a number of protein functions in the prevention of numerous types of epithelial-to-mesenchymal transition (EMT)-driven fibrosis in vivo. However, relatively little is known regarding its effect in the EMT of the renal tubular epithelial cells, which play an important role in renal tubulointerstitial fibrosis and is an important component of the renal injury that is associated with diabetic nephropathy. The present study investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Hence it often acts as a mesenchymal marker in renal fibrosis [34]. As shown in Figure 5b,c, the reduction of E-ca protein expression in HG conditions was accompanied by an increase of α-SMA protein expression, which was close associated with our preliminary experiments, and confirmed that HG promotes EMT development in NRK-52E cells [35]. However, HG-induced EMT was decreased after pre-treating the NRK-52E cells with BBR, these demonstrated that BBR could reduce α-SMA and E-ca expression together.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Hence it often acts as a mesenchymal marker in renal fibrosis [34]. As shown in Figure 5b,c, the reduction of E-ca protein expression in HG conditions was accompanied by an increase of α-SMA protein expression, which was close associated with our preliminary experiments, and confirmed that HG promotes EMT development in NRK-52E cells [35]. However, HG-induced EMT was decreased after pre-treating the NRK-52E cells with BBR, these demonstrated that BBR could reduce α-SMA and E-ca expression together.…”
Section: Resultssupporting
confidence: 79%
“…A previous study demonstrates that BBR treatment may be related with AMPK pathway together with Nrf2 pathway may lead to the increase of NQO1 and HO-1 in both LPS-shocked macrophages and mice, and that means AMPK is a upstream of Nrf2 [52]. In addition, BBR can induce the activation of PI3K/Akt and p38 pathway, which both can upregulate the expression and activity of HO-1 as well as NQO1 [35]. Moreover, other studies have revealed that BBR as an Nrf2 activator against glucose neurotoxicity so that attenuating high glucose-induced neurotoxicity, these findings provided another potential therapeutic use of BBR on the treatment of diabetic complications [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact role of EMT in renal fibrosis remains to be established [24], it is widely believed that renal tubular EMT is one of the critical factors mediating RIF. Oxidative stress damage is associated with the pathogenesis of RIF by tubular EMT [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we found that in the absence of ZnT4, Akt expression was much lower in the lactating mammary gland. Accumulation of intracellular Zn decreases Akt expression (53), and the inability to mobilize Zn pools from the Golgi apparatus may also reduce Akt signaling (47). Whether reduced Akt expression in C57BL/6J lm/lm mice was a direct effect of dysregulated Zn homeostasis in the Golgi apparatus, global defects in Golgi organization and signaling scaffolds (35), ZnT2-mediated Zn accumulation into vesicles withholding Zn from activating Akt phosphorylation, or further alterations in cellular Zn homeostasis, is not currently understood.…”
Section: Ck8mentioning
confidence: 99%